SYSTEMS, APPARATUS, AND METHODS FOR STABILIZATION AND BLENDING OF EXPOSURES (2022)
Systems, apparatus, and methods for stabilization and blending of exposures. So-called Electronic Image Stabilization (EIS) techniques use image manipulation software to compensate for camera motion. Unfortunately, existing EIS techniques cannot compensate for artifacts introduced by low shutter speed (e.g., blurs). Various embodiments of the present disclosure generate stabilized images from multiple exposures. In one exemplary embodiment, the stabilized exposures are blended using a linear sum of the color data for each pixel of the image. By stabilizing each exposure and linearly summing the light information, the camera shake can be removed, and the subject motion blur can be controlled. The stabilization and blending techniques enable a mathematical emulation of a selected shutter angle from many high-speed exposures.